Kinetics and mechanism of the electrochemical reduction of NO2+ in concentrated sulphuric acid - Calandra, Alfredo J. (1972)
The electrochemical reduction on gold of NO2+ dissolved in concentrated H2SO2 has been studied by means of the rotating disk electrode and cyclic voltammetry, over a wide range of experimental conditions. The kinetic parameters are interpreted in terms of the following reaction mechanism, [fórmula]